Effects of Relative Cane Hardness on Oboe Reeds - Conjurske, Jonathan; Esser, Alexandra; Johnston, Katelyn (My University, 2013)
Oboists rely heavily on the quality of their reeds; therefore, consistency in reed making is crucial. The purpose of this study was to investigate if the relative can hardness affects the outcome of a finished oboe reed.
Color poster with text and graphs.
Keywords: Oboe reeds--Quality of; Posters